1985
DOI: 10.1177/074823378500100417
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Acceptable Factor To Estimate Chronic End Points From Acute Toxicity Data

Abstract: Acceptable daily intake (ADI) values are routinely developed for threshold toxicants from NOAELs determined from human or animal chronic or subchronic data. These NOAELs are then divided by appropriate uncertainty factors ranging from 10 to 1000 depending on the quality of the data. However, for the vast majority of chemicals used industrially, adequate toxicity data needed to use this process are not available. Thus, a procedure to estimate a chronic toxicity endpoint from acute toxicity data, such as an oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…[23][24][25][26][27] Our studies demonstrated that feeding StemEnhance at 600 mg/kg for 2 weeks was not toxic to Wistar rats. StemEnhance did not affect the behavior or physical examinations of the rats.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] Our studies demonstrated that feeding StemEnhance at 600 mg/kg for 2 weeks was not toxic to Wistar rats. StemEnhance did not affect the behavior or physical examinations of the rats.…”
Section: Discussionmentioning
confidence: 99%
“…Venman and Flaga (1985) compared oral LD50 values for compounds to their respective NOAEL values from long-term repeat-dose studies. Since the LD50 value represents a dose consistent with a very severe endpoint, it is understandable that a MF much greater than that applied to a NOAEL value should be used when deriving a TI based on an LD50 value rather than a NOAEL value.…”
Section: Use Of Ld50 Values As the Basis For The Timentioning
confidence: 99%
“…To hedge against the tendency to neglect chemicals that have been incompletely tested (Gray, Brand, & Evans, 1997), we explore the potential for estimating a potency factor from a more readily available acute toxicity measure. Venman and Flaga (1985) and Layton et al (1987), for example, suggested that readily available lethal dose data could provide a basis for estimating measures such as the effect dose ED 10h .…”
Section: Estimation Of βEd10 Through Extrapolationmentioning
confidence: 99%